Evaluation of rheumatologists’ knowledge of biosimilars - Thayane Furtado Rolim Lima; Lia Poti Gomes Cordeiro; Kirla Wagner Poti Gomes; Carlos Ewerton Maia Rodrigues (Advances in Rheumatology)
Abstract Introduction Biosimilars reduce the cost of biologic therapy without compromising safety and effectiveness. In this study we evaluated Brazilian rheumatologists’ knowledge and perceptions of biosimilars. Methods Cross-sectional and descriptive study based on a questionnaire containing 17 items on familiarity, knowledge and perceptions of biosimilars. Results Answers were received from 135 rheumatologists, of whom 97.8% were familiar with biosimilars and 92.5% had at some time prescribed them, but only 47.7% felt comfortable prescribing them to stable patients and 62.2% strongly disagreed with automatic substitution. In addition, 51.9% preferred naive patients when starting treatment with biosimilars. Conclusion Despite the growing acceptance of biosimilars, many physicians remain reluctant. Evidence-based continuing education is essential to clarify these issues.